Older Hospitalised Patients' Reported Confidence in Managing Discharge Needs: a Retrospective Observational Study - Romero-Ortuno, Roman (My University, 2023)
Objectives: To evaluate the introduction of a patient-reported outcome measure (PROM) of self-confidence in managing discharge needs in an acutely hospitalised older adult population. Methods: A retrospective service evaluation in an English hospital. The PROM measure consisted of a visual analogue scale asking patients to rate their confidence with managing the things that they would need to do at home. This was collected on admission and discharge. Results: Of 923 patients, 461 had both admission and discharge confidence scores. Median confidence was higher at discharge (8.00, IQR: 6.20-9.80) than on admission (7.20, 5.00-9.00) (P<0.001). Predictors of high confidence with managing discharge needs at admission were: being male; having a lower number of morbidities; self-reporting fewer falls over the last year; and a higher level of functional mobility. Low confidence score on admission, being from one’s own home, and a higher number of physiotherapy contacts were associated with improvement in PROM scores. Self-confidence in managing discharge needs at discharge was not associated with readmission within 30 days. Conclusions: Measuring patient-reported confidence to manage discharge needs is feasible in an older inpatient population. Confidence improved from admission to discharge, and more frequent physiotherapy input was associated with improved confidence.
PUBLISHED
Keywords: Aged; Confidence; Hospital; Patient Reported Outcome Measure; Ageing; AGEING; Age-related disability; Third age/ageing